TELESCOPIC“ INGOTS ARE REALITY - E. I. Marukovich; V. I. Baranov; Ju. L. Staniulenis (Литьë и металлургия, 2006)
The article describes technological peculiarities of production of continuously-cast ingots by continuous horizontal method of casting into benched crystallizer.